2018
DOI: 10.1021/acsaem.7b00220
|View full text |Cite
|
Sign up to set email alerts
|

Operando Micro-Raman Study Revealing Enhanced Connectivity of Plasmonic Metals Decorated Silicon Anodes for Lithium-Ion Batteries

Abstract: The efficient formulation of silicon based, highloading electrode with good capacity retention and cycling stability remains challenging. To gain a better understanding of the ongoing processes and failure mechanisms occurring during battery performance, operando micro-Raman spectroscopy is helpful to map the active silicon sites. Herein, we present the investigation of the electrochemical performance of anodes composed of plasmonic metal (Ag and Au) decorated silicon, designed for enhancing Raman signal. Foll… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 42 publications
0
15
0
Order By: Relevance
“…Because electrodes and electrolytes are the two main components in all batteries, breakthroughs in these components are essential for the development of high-performance batteries, including LIBs, Li-S batteries, etc. [366][367][368] To improve the performance of high-capacity alloy material batteries, the electrochemical reaction processes, structural evolution, and degradation mechanisms should be systematically investigated. In recent years, in situ and operando characterizations (such as in situ SEM/TEM, operando X-ray diffractometer (XRD), cryogenic electron microscopy, X-ray, neutron reflectometry, etc.)…”
Section: Advanced In Situ/operando Characterizations On Silicon-basedmentioning
confidence: 99%
“…Because electrodes and electrolytes are the two main components in all batteries, breakthroughs in these components are essential for the development of high-performance batteries, including LIBs, Li-S batteries, etc. [366][367][368] To improve the performance of high-capacity alloy material batteries, the electrochemical reaction processes, structural evolution, and degradation mechanisms should be systematically investigated. In recent years, in situ and operando characterizations (such as in situ SEM/TEM, operando X-ray diffractometer (XRD), cryogenic electron microscopy, X-ray, neutron reflectometry, etc.)…”
Section: Advanced In Situ/operando Characterizations On Silicon-basedmentioning
confidence: 99%
“…The Si@Cu composite electrodes possessed the capacity retention with approximately 240 mAh g −1 after 20 cycles. Miroshnikov et al confirmed that the metal coatedlayer could enhance the interconnectivity of the Si particles by almost 50% which increased the ratio of electroactive Si and enhanced the cyclability of Si-based anode materials [15] . However, the reported synthetic method possesses complex preparation processes and expensive instruments and raw materials.…”
Section: Methodsmentioning
confidence: 99%
“…The continuous volume change from the repeated Li-Si lithiation/delithiation processes eventually result in the crack of the coating layer and the separation of Si with conductive carbon, which leads to the continuous formation of excess SEI films, thus deteriorating ultimately the cycling performance. To address this issue, the metal coated layer with high conductivity and excellent ductility has been developed for improving both the conductivity and cyclability of Si-based electrodes [15][16][17] . For example, Yin et al prepared nanostructured Si@Ag composites via directly mixing Si and Ag nanoparticles through ultrasonication in ethanol and drying processes, which exhibited stable electrode integrality and cycling performance compared with Si Scheme 1.…”
Section: Introductionmentioning
confidence: 99%
“…However, the behavior of molecular species at these electroactive interfaces has been poorly investigated by SERS. [32][33][34][35][36][37][38][39] Herein, we introduce rhodamine B into the ester-based electrolyte for Li/graphite cells and in situ monitor the molecular behavior of RhB on the graphite/electrolyte interface by SERS. Cycle and rate performances were improved with the addition of 0.2 wt% RhB.…”
Section: Introductionmentioning
confidence: 99%